Methods of Pedagogical Control of Motor Abilities Development in Seventh-Ninth Grade Boys - О. В. Іващенко; С. С. Єрмаков; Т. В. Карпунець; Ю. В. Крінін; С. В. Назаренко (OVS LLC, 2015)
The research objective is to define methodological approaches to pedagogical control of the level of motor abilities development in middle schoolers. Materials and methods. To achieve the objectives set, the research relied on following methods used: analysis of scientific and methodological literature, pedagogical testing and methods of mathematical statistics. The participants in the study were 24 seventh grade boys, 17 eighth grade boys, and 17 ninth grade boys. Research results. The discriminant function can serve as a classifier for the age peculiarities of motor and functional readiness in seventh-ninth grade boys. The discriminant function equations allow to correctly classify 95.8% of the grouped data. The priority in the factor structure of readiness of the seventh grade boys belongs to the functional, coordination and strength readiness. For the eighth grade boys, it is functional, coordination and strength readiness, and for the ninth grade boys - strength, functional and coordination readiness. Conclusions. The final pedagogical control of motor and functional readiness of the seventh grade boys can use the first discriminant function with emphasis on the most informative variables. Such physical education can be considered effective if the results shown by the seventh grade boys  are classified as results similar to those displayed by the eighth grade boys. In the final pedagogical control of motor and functional readiness in eighth grade boys, the reference point is the results of the ninth grade boys with emphasis on the most informative indicators of the discriminant function.